Interval-Valued Neutrosophic Soft Rough Sets. (19th January 2015) - Broumi, Said; Smarandache, Flornetin
Abstract : We first defined interval-valued neutrosophic soft rough sets (IVN-soft rough sets for short) which combine interval-valued neutrosophic soft set and rough sets and studied some of its basic properties. This concept is an extension of interval-valued intuitionistic fuzzy soft rough sets (IVIF-soft rough sets).